Origami Based Cargo Drone - Abhinav Ajay; Amal Prakash J; Gokul S; Sneha Aji; Poorna R Prabhu (Journal of Electronic Design Engineering, 2019)
A revolution in parcel delivery is created by multicopters, because of their capability to operate in isolated areas, unsuitable road infrastructure, and calamity affected areas etc. But current multicopters used for parcel delivery are dangerous to people, and are also difficult to store and transport, that is the current multicopters are not much user-friendly. Safety issues arise due to the unshielded spinning propellers, which is injurious to the user. Transportation at the time of deployment and storage is often impaired by its large size which is required for heavy lifting. This paper addresses the limitations of the current multicopter by proposing the integration of a quadcopter into a foldable protective cage. A protective structure is provided by the cage which physically separates the propellers from the environment, and it also ensures the safety of people. The size of the cage can be reduced by folding, that provides ease of storage and transportation.